Features of development of maximum and explosive strength in weightlifting groups of sports improvement and higher sports skill - S.A. Pogrebnyak; I.N. Nikulin; F.I. Sobyanin; I.N. Belousova (Theory and Practice of Physical Culture, 2023)
Objective of the study was to experimentally test the method of strength training of weightlifters in the groups of sports improvement and higher sportsmanship using the static-dynamic method and plyometric exercises. Methods and structure of the study. Five weightlifters with the sports title "Master of Sports of Russia" and 11 weightlifters with the sports title "Candidate for Master of Sports" participated in the experiment. The consecutive pedagogical experiment lasted four months, of which two months were the ascertaining part and two months were allotted for the forming part with the use of experimental factors. Athletes trained five times in a weekly microcycle. The peculiarity of the experimental methodology was the inclusion in the main part of the training session of weightlifters of exercises performed using the static-dynamic method using 60-90% of the load from a single maximum. In addition, weightlifters used exercises performed by the plyometric method. Various types of jumps and arm extensions were used. At each training session, one or two exercises were performed in three series, consisting of 5-10 repetitions. Results and conclusions. In all tests of the experimental stage of the study, a significant increase in the results was found. The greatest increase in results, exceeding 5%, was established in terms of the manifestation of maximum and explosive strength: “High jump according to Abalakov” (8%, p<0.05); "Bar deadlift" (5.4%, p<0.01); "Long jump from a place" (5.2%, p<0.01), as well as in the competitive exercises "Classic push" (5.2%, p<0.01); "Classic "Classic jerk" (4.3%, p<0.05). According to the results of the correlation analysis of strength indicators in competitive exercises (snatch and clean and jerk), in comparison with the control ones, a strong positive relationship was revealed: in the deadlift of the barbell, in squats with a barbell on the chest and long jump from a place. A moderate positive relationship was observed in the control test “High jump from a place according to the method of V.M. Abalakov.